FAKTOR – FAKTOR INTERNAL DAN EKSTERNAL MANAJEMEN MUTU PENDIDIKAN ISLAM - Amruzziyad; Mahyudin; M. Sobry (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Quality management in Islamic education is a systematic effort to ensure and improve the quality of educational processes and outcomes based on Islamic values. This study aims to identify and analyze the internal and external factors that influence the success of quality management in Islamic educational institutions. Internal factors include the leadership of the headmaster, teacher competence, Islamic value–based curriculum, infrastructure, and Islamic organizational culture. Meanwhile, external factors consist of government policies, the role of society and parents, technological developments, and social and economic dynamics. The research method employed is a literature study with a descriptive-analytical approach based on various relevant sources, including theories of educational quality management and the context of Islamic education. The results indicate that synergy between internal and external factors greatly determines the sustainability and effectiveness of quality management implementation in Islamic educational institutions. Therefore, strengthening internal institutional capacity and establishing strategic collaboration with external stakeholders are key to creating superior, relevant, and competitive Islamic education quality.